International Brands on The Local Market – Consumer Purchase Decisions - Bartlomiej KABAJA (Communications of International Proceedings, 2021)
The aim of the study was to determine consumer preferences in terms of purchasing cola-flavored carbonated drinks by conducting a thorough analysis of the respondents’ behavior. The study comprised 60 adult respondents: 27 women (45%) and 33 men (55%). The selection of the study sample was random. The research was conducted in September 2020. The adopted research procedure assumed the use of eye-tracking methods. The research results show that Coca-Cola was the most frequently chosen cola-flavored carbonated drink among the participants of the study. The conducted research confirms how much attention and recognition accompany brands with a global reach. Local brands of the carbonated drinks segment will probably have to carry out more targeted marketing and PR activities to increase their share in this market.
Keywords: Brand; Globalization; Product; Beverages.